General coupled fixed point theorem for a nonlinear contractive condition in a cone metric space - Bhaumik, Shantanu; Tiwari, Surendra Kumar (Eurasian Mathematical Journal, 2018)
The existence and uniqueness of coupled fixed point theorem has been proved under various contractive condition in a cone metric space. The result is verified with the help of suitable example.